Human rights in Indian situation - "Benjamin, Joseph" (New Delhi, 2008)
The present book envisages to analyse holistically how Human Rights are being brazenly violated in spite of various Commissions constituted by government of India like Commission for Linguistic Minority in India (Ministry of Social Justice, Government of India), National Commission for Religious and Linguistic Minorities, National Minority Commission, National Commission for Women, National Commission for Protection of Child Rights etc. The target groups are Dalit, Women, Religious Minorities and Children in India. Yet the list does not exhaust other groups, which face the onslaught of societal privileged class or suffer in limbo due to high or low degree of central of state government and bureaucratic apathy. This book would be an eye opener for governmental bodies, bureaucrats, and NGOs. Almost all commissions are stationed in New Delhi and may not know what is happening in the rural areas. The writer would be happy to have comments and feedback on this book on Human Rights, which has and is becoming an important issue in the arena of political discourse, nationally and internationally giving a short shrift to national boundaries.
Keywords: Human rights-India